2019
DOI: 10.1103/physrevb.100.140412
|View full text |Cite
|
Sign up to set email alerts
|

Direct coupling of ferromagnetic moment and ferroelectric polarization in BiFeO3

Abstract: The spin-driven component of electric polarization in a single crystal of multiferroic BiFeO3 was experimentally investigated in pulsed high magnetic fields up to 41 T. Sequential measurements of electric polarization for various magnetic field directions provide clear evidence of electric polarization normal to the hexagonal c axis (Pt) in not only the cycloidal phase, but also the field-induced canted antiferromagnetic phase. The direction of Pt is directly coupled with the ferromagnetic moment in the canted… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…This fieldinduced rearrangment of the cycloidal domains was found to be responsible for the nonvolatile change in the transverse polarization [30,31]. A magnetoelectric term quadratic in spins was suggested to describe the magnetic order induced polarization within the (111) plane [31], which was confirmed very recently by high-field magneto-current measurements [32].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…This fieldinduced rearrangment of the cycloidal domains was found to be responsible for the nonvolatile change in the transverse polarization [30,31]. A magnetoelectric term quadratic in spins was suggested to describe the magnetic order induced polarization within the (111) plane [31], which was confirmed very recently by high-field magneto-current measurements [32].…”
Section: Introductionmentioning
confidence: 70%
“…1 , and (1,2) 2 in Table IV) suggests that either anisotropic spin current or higher order anisotropy terms may play a role. These interactions are also relevant in the description of the static magnetoelectric effect [30,32,52]. Indeed, additional ANI terms allowed us to reproduce the NDD signal observed for k X.…”
mentioning
confidence: 92%
“…In various other reports, including using ESR measurements, [ 215 ] and using high applied magnetic fields on bulk single crystals, a critical field of H cr ≈ 18 T has been found. [ 215–218 ]…”
Section: Perturbations To the Cycloidmentioning
confidence: 99%
“…[ 217 ] These authors further explored the angular dependence of applied magnetic fields and revealed a polarization orthogonal to the [111] direction, strongly coupled to the cycloid. [ 216,218 ] The suppression of the cycloid and the associated transverse polarization could be intrinsically linked to the increased magnitude of the [111] polarization above the critical field. This is in contrast with other reports in which the magnitude of polarization decreases upon reaching the homogeneous G‐type AFM order.…”
Section: Perturbations To the Cycloidmentioning
confidence: 99%
“…Hence, it is crucial to realize past discoveries, present challenges and strategize for the future. The relation between the electric and magnetic subsystems can vary among the materials and also existing conditions; for instance, Bismuth ferrite theoretically, at room temperature shows quadratic and higher-order relation, while a linear behavior is observed at application with high electric fields or magnetic fields around 10-18 T [1,2], for the bulk and about 3-6 T for thin film samples depending upon their substrate [3]. Recently there have been many review papers related to Bismuth ferrite (BFO) [4][5][6][7] and its magnetoelectric coupling but this paper stands out from the rest in providing theoretical background and practical knowledge needed in a way that could be understood by a reader who is even new to the topic.…”
Section: Introductionmentioning
confidence: 99%